2019
DOI: 10.1016/j.jcrc.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of very old patients admitted to intensive care unit after acute versus elective surgery or intervention

Abstract: Background: We aimed to evaluate differences in outcome between patients admitted to intensive care unit (ICU) after elective versus acute surgery in a multinational cohort of very old patients (≥80 years; VIP). Predictors of mortality, with special emphasis on frailty, were assessed. Methods: In total, 5063 VIPs were included in this analysis, 922 were admitted after elective surgery or intervention, 4141 acutely, with 402 after acute surgery. Differences were calculated using Mann-Whitney-U test and Wilcoxon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…1 ). Elective patients from VIP1 were specifically excluded as they significantly differ from acutely admitted patients in risk distribution and outcomes as previously shown 17 . The primary endpoint of this study was 30-day-mortality.…”
Section: Methodsmentioning
confidence: 99%
“…1 ). Elective patients from VIP1 were specifically excluded as they significantly differ from acutely admitted patients in risk distribution and outcomes as previously shown 17 . The primary endpoint of this study was 30-day-mortality.…”
Section: Methodsmentioning
confidence: 99%
“…To our knowledge, this is the first study to compare frequencies of therapeutic interventions, limitations on life-supporting treatments, risk factors for mortality, and outcomes between VIPs admitted with sepsis and those admitted for other acute reasons. In the present study, elective surgical patients were excluded because various other publications [23,[28][29][30][31][32] demonstrated that such patients have a better outcome with much lower mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…First, planned admissions have a much better prognosis, and these admissions must be analyzed separately. 36 The patients admitted after scheduled surgery are highly selected: they agree for a risky surgical procedure, anesthetists and surgeons agree to perform surgery, and very few have a limitation of lifesustaining treatment (LST). 37 It should be emphasized that the influence of frailty was more important than the age expressed per period of 5 years to predict 1-month survival.…”
Section: Outcome Survivalmentioning
confidence: 99%